diff --git a/CommAlg/final_poly_type.lean b/CommAlg/final_poly_type.lean index 1cc5c48..1a7eb77 100644 --- a/CommAlg/final_poly_type.lean +++ b/CommAlg/final_poly_type.lean @@ -86,12 +86,29 @@ lemma Poly_constant (F : Polynomial ℚ) (c : ℚ) : simp · sorry +-- Get the polynomial G (X) = F (X + s) from the polynomial F(X) +lemma Polynomial_shifting (F : Polynomial ℚ) (s : ℚ) : ∃ (G : Polynomial ℚ), (∀ (x : ℚ), Polynomial.eval x G = Polynomial.eval (x + s) F) ∧ (Polynomial.degree G = Polynomial.degree F) := by + sorry + -- Shifting doesn't change the polynomial type lemma Poly_shifting (f : ℤ → ℤ) (g : ℤ → ℤ) (hf : PolyType f d) (s : ℤ) (hfg : ∀ (n : ℤ), f (n + s) = g (n)) : PolyType g d := by simp only [PolyType] rcases hf with ⟨F, hh⟩ - rcases hh with ⟨N,ss⟩ - sorry + rcases hh with ⟨N,s1, s2⟩ + have this : ∃ (G : Polynomial ℚ), (∀ (x : ℚ), Polynomial.eval x G = Polynomial.eval (x + s) F) ∧ (Polynomial.degree G = Polynomial.degree F) := by + exact Polynomial_shifting F s + rcases this with ⟨Poly, h1, h2⟩ + use Poly + use N + constructor + · intro n + specialize s1 (n + s) + intro hN + have this1 : f (n + s) = Polynomial.eval (n + s : ℚ) F := by + sorry + sorry + · rw [h2, s2] + -- PolyType 0 = constant function lemma PolyType_0 (f : ℤ → ℤ) : (PolyType f 0) ↔ (∃ (c : ℤ), ∃ (N : ℤ), (∀ (n : ℤ), @@ -143,7 +160,17 @@ lemma foofoo (d : ℕ) : (f : ℤ → ℤ) → (PolyType f d) → (PolyType (Δ lemma Δ_d_PolyType_d_to_PolyType_0 (f : ℤ → ℤ) (d : ℕ): PolyType f d → PolyType (Δ f d) 0 := fun h => (foofoo d f) h -lemma foofoofoo (d : ℕ) : (f : ℤ → ℤ) → (∃ (c : ℤ), ∃ (N : ℤ), (∀ (n : ℤ), N ≤ n → (Δ f d) (n) = c) ∧ c ≠ 0) → (PolyType f d) := by +-- The "reverse" of Δ of 1 times increases the polynomial type by one +lemma Δ_1_ (f : ℤ → ℤ) (d : ℕ) : PolyType (Δ f 1) d → PolyType f (d + 1) := by + intro h + simp only [PolyType, Nat.cast_add, Nat.cast_one, exists_and_right] + rcases h with ⟨P, N, h⟩ + rcases h with ⟨h1, h2⟩ + let G := fun (q : ℤ) => f (N) + sorry + + +lemma foo (d : ℕ) : (f : ℤ → ℤ) → (∃ (c : ℤ), ∃ (N : ℤ), (∀ (n : ℤ), N ≤ n → (Δ f d) (n) = c) ∧ c ≠ 0) → (PolyType f d) := by induction' d with d hd -- Base case @@ -160,7 +187,23 @@ lemma foofoofoo (d : ℕ) : (f : ℤ → ℤ) → (∃ (c : ℤ), ∃ (N : ℤ), intro h rcases h with ⟨c, N, h⟩ have this : PolyType f (d + 1) := by - sorry + rcases h with ⟨H,c0⟩ + let g := (Δ f 1) + -- let g := fun (x : ℤ) => (f (x + 1) - f (x)) + have this1 : (∃ (c : ℤ), ∃ (N : ℤ), (∀ (n : ℤ), N ≤ n → (Δ g d) (n) = c) ∧ c ≠ 0) := by + use c; use N + constructor + · intro n + specialize H n + intro h + have this : Δ f (d + 1) n = c := by tauto + rw [←this] + rw [Δ_1_s_equiv_Δ_s_1] + · tauto + have this2 : PolyType g d := by + apply hd + tauto + exact Δ_1_ f d this2 tauto -- [BH, 4.1.2] (a) => (b)